Whāea Betty Wark: From Uncertain Beginnings to Honoured Community Worker - Connor, Helene (Waka Kuaka, 2014)
Whāea or “Ma” Betty Wark was a Māori woman who was actively involved with community-based organisations from the 1950s until her death in May 2001. She was particularly well-known as being one of the founders of Arohanui Incorporated which was established in 1976. Its main purpose was to provide accommodation for young homeless Māori and others in need.